MEAT PRODUCTION, TRADE, CONSUMPTION AND SELF-SUFFICIENCY RATE IN ROMANIA IN THE PERIOD 2014-2022 - Agatha POPESCU; Mirela STANCIU; Olga DRĂGHICI; Horia Nicolae CIOCAN; Valentin SERBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The goal of the study is to analyze the dynamics of meat production, import, export, availability for human consumption and self-sufficiency rate (SSR) in Romania in the period 2014-2022 based on the data provided by National Institute of Statistics. The empirical data were processed using the growth rate, trend regression equations, determination coefficient, illustrative graphical representations and tabled results for the indicators taken into consideration. The results highlighted that in the studied period, total meat production (in fresh meat equivalent), decreased by 22.5%, from 1,291.9 thousand tons in 2014 to 1,001.6 thousand tons in 2022. But, by meat sort, the situation is different as follows: bovine meat production declined by 8.9% and pork production by - 16.4%, while sheep and goat meat increased by 27.2% and poultry meat by 43.8%. The imported quantities of meat registered an ascending trend from 383.9 thousand tons in 2024 to 628.5% in 2022 (+63.7%). By meat sort, the imported amounts increased by 12.4% for beef, by 200% for pork, by 400% for sheep and goat meat and by 8.1% in case of poultry meat. In 2022, Romania exported 166.8 thousand tons meat meaning by 31.61% more than in 2014. By meat type, the exported amounts increased by 200% for bovine meat, by 86 % in case of sheep and goat meat, by 45.2% in case of poultry meat, but in case of pork declined by 36%. The meat availability for consumption increased by 22.4% from 1,150.6 thousand tons in 2014 to 1,463.3 thousand tons in 2022. For total meat, self-sufficiency rate (SSR) declined from 83.3% in 2014 to 68.4% in 2022. By meat sort, SSR went up for bovine meat accounting for 87.1% in 2022 versus 82.1% in 2014, for pork SSR went down to 45.4% in 2022 versus 70.2% in 2014, SSR for sheep and goat meat was 100% in 2022 versus 106% in 2014 and for poultry meat, SSR increased from 87.5% to 95.2% in the studied period. In 2022, a Romanian consumed in average 74 kg meat, of which 38 kg pork, 27.9 kg poultry meat, 5 kg beef and veal and 2.6 kg sheep and goat meat, much more than in 2014, except bovine meat. As a conclusion, imports sustain pork domestic market as production is not enough to cover the demand, but also in smaller amounts for the other meat types. Romania is also an exporting country of meat, as long as the availability of meat on the internal market is raising.